Given equation is "(p-q)z = z^2 + (x+y)^2"
Comparing above equation with "Pp + Qq = R"
Then
"\\frac{dx}{z}=\\frac{dy}{-z}=\\frac{dz}{z^2 + (x+y)^2}"
Taking first two,
"\\frac{dx}{z} = - \\frac{dy}{z}"
Integrating both sides,
"x = - y + C"
"x+y = C" (1)
Then taking first and last,
"\\frac{dx}{z} = \\frac{dz}{z^2+(x+y)^2}"
"\\frac{dx}{z} = \\frac{dz}{z^2+C^2}"
Integrating both sides
"\\int {dx}=\\int \\frac{zdz}{z^2+C^2}"
"x = \\frac{1}{2}log|z^2 + C^2| + log|b|"
then "b = (z^2 + (x+y)^2)e^{-2x}"
Hence,
solution of the equation will be
"f(x+y) = (z^2 + (x+y)^2)e^{-2x}"
Comments
Leave a comment